Sex-Related Differences in the Effects of the Mediterranean Diet on Glucose and Insulin Homeostasis - Alexandra Bédard; Louise Corneau; Benoît Lamarche; Sylvie Dodin; Simone Lemieux (Journal of Nutrition and Metabolism)
Objective. To document sex differences in the impact of the Mediterranean diet (MedDiet) on glucose/insulin homeostasis and to verify whether these sex-related effects were associated with changes in nonesterified fatty acids (NEFA). Methods. All foods were provided to 38 men and 32 premenopausal women (24–53 y) during 4 weeks. Variables were measured during a 180 min OGTT before and after the MedDiet. Results. A sex-by-time interaction for plasma insulin iAUC was found (men: −17.8%, P=0.02; women: +9.4%, P=0.63; P for sex-by-time interaction = 0.005). A sex-by-time interaction was also observed for insulin sensitivity (Cederholm index, P=0.03), for which only men experienced improvements (men: +8.1%, P=0.047; women: −5.9%, P=0.94). No sex difference was observed for glucose and C-peptide responses. Trends toward a decrease in NEFA AUC (P=0.06) and an increase in NEFA suppression rate (P=0.06) were noted, with no sex difference. Changes in NEFA were not associated with change in insulin sensitivity. Conclusions. Results suggest that the more favorable changes in glucose/insulin homeostasis observed in men compared to women in response to the MedDiet are not explained by sex differences in NEFA response. This clinical trial is registered with clinicaltrials.gov NCT01293344.